Functional Characterization of Two Thioredoxin Proteins of Toxoplasma gondii Using the CRISPR-Cas9 System - Zhang, Zhi-Wei; Li, Ting-Ting; Wang, Jin-Lei; Liang, Qin-Li; Zhang, Hai-Sheng; Sun, Li-Xiu; Zhu, Xing-Quan (Frontiers in Veterinary Science, 2021)
Toxoplasmosis caused by infection with Toxoplasma gondii is an important parasitic zoonosis with a worldwide distribution. In this study, we examined the functions of two thioredoxins (namely CTrp26 and CTrx1) of T. gondii tachyzoites by generation of HA tag strains or gene deficient parasites in Type I RH strain (ToxoDB#10). Immunofluorescence analysis (IFA) was used to investigate the subcellular localization of the thioredoxins (Trxs). Results of IFA showed that both CTrp26 and CTrx1 were located in the cytoplasm of T. gondii. Functional characterizations of CTrp26 and CTrx1-deficient parasites were performed by plaque assay, intracellular replication, egress, H2O2 resistance, detection of reactive oxygen species (ROS) level and total antioxidant capacity (T-AOC) assays in vitro, as well as mouse infection in vivo. Our results showed that deletion of CTrp26 or CTrx1 did not influence the ability of T. gondii RH strain to replicate, egress, form plaque, resist H2O2 exposure, maintain the ROS level and T-AOC, and also did not serve as virulence factors in Kunming mice. Taken together, these results provide new properties of the two Trxs. Although they are not essential for RH strain, they may have roles in other strains of this parasite due to their different expression patterns, which warrants future research.